(untitled) (Journal of Architectural Design, 2022)
The article describes the results of experimental studies to identify the effect of polycarboxylate plasticizers on the properties and structure of a gypsum binder obtained from used moulds for casting sanitary faience. It has been established that the introduction of a new generation of polycarboxylate modifiers into the binder in an amount of 0.5 to 1.5% can increase its strength by 1.7 - 2.4 times